Vitamin D(3) enhanced intestinal phosphate cotransporter genes in young and growing broilers - Aye Cho, Tay-Zar (Poult Sci, 2020)
The influence of dietary vitamin D(3) (VD3) levels on growth, bone performance, and duodenal type IIb sodium-dependent phosphate cotransporter (NaPi-IIb) genes in broiler chicken were studied. One-day-old male Ross308 broilers (n = 432) were allocated into 6 treatment groups with each group consisting of 6 cage pens. Each treatment group received diet containing different amounts of VD3 (80, 200, 500, 1,250, 3,125, or 7,813 IU per kg of diet) from a day-old to 31 D of age. Dietary available phosphorus and calcium were kept the same across all treatments in each phase. At 14 D, influence of VD3 on BW gain was found in the birds that received VD3 of 3,125 IU/kg and 200 IU/kg (P < 0.05). Toe ash and tibia ash linearly increased (P < 0.05) at 14 D with increase in dietary VD3(.) There was no significant influence of dietary VD3 on tibia breaking strength. In both phases, relative expression of duodenal NaPi-IIb linearly increased (P < 0.01) with increase in dietary VD3. At 14 D, highest expression of 3.2 folds was observed in birds treated with VD3 at 7,813 IU/kg of feed. At 31 D, birds that received VD3 levels of 3,125 and 7,813 IU/kg of feed showed 2.9 folds higher in NaPi-IIb expression compared with those fed lowest level of VD3 at 80 IU/kg of feed. When dietary calcium and phosphorus were maintained at the standard requirement, increase in dietary VD3 did not improve growth performance. For optimum growth and bone characteristics, dietary inclusion of VD3 at 500 IU/kg was adequate for both starter and grower broiler diets. Vitamin D(3) enhanced the expression of NaPi-IIb at higher doses and thus improving the tibia ash content in high VD3 treatment groups. This study reported for the first time an increased in the expression of duodenal NaPi-IIb in 31-day-old broilers in response to high dietary VD3 levels.